Pengaruh Kepuasan Kerja, Disiplin Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada CV Reyhan Anugrah Packaging Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
This study aims to analyze the influence of job satisfaction, work discipline, and organizational commitment on employee performance at CV Reyhan Anugrah Packaging Denpasar, involving all 42 employees as the sample using a census method. Data were collected through observation, interviews, documentation, and questionnaires based on a Likert scale, then processed using SPSS 25 with multiple linear regression analysis. The results show that job satisfaction, work discipline, and organizational commitment each have a positive and significant effect on performance, and simultaneously, all three also significantly improve employee performance. Therefore, the company is advised to continuously enhance job satisfaction, enforce discipline, and strengthen organizational commitment in order to optimize employee productivity and achieve corporate goals more effectively